Continuous intraoperative nerve monitoring in thyroidectomy using automatic periodic stimulation in 256 at-risk nerves - Hamilton, N (Ann R Coll Surg Engl, 2019)
INTRODUCTION: Automatic periodic stimulation of the vagal nerve during thyroidectomy provides real-time feedback of recurrent laryngeal nerve function intraoperatively. To assess the validity of this device, the ability of monitoring to predict recurrent laryngeal nerve palsy was determined and the incidence of recurrent laryngeal nerve palsy recorded. MATERIALS AND METHODS: All thyroidectomies using APS® (Automatic Periodic Stimulation, Medtronic) nerve monitoring were reviewed over a 27-month period. Changes in signal amplitude and latency during thyroidectomy were recorded from saved data. Postoperative fibreoptic laryngoscopy determined the incidence of vocal cord immobility and recovery of nerve function was assessed from follow-up letters. RESULTS: A total of 256 at-risk nerves were examined (132 hemi- and 62 total thyroidectomies) in cases involving benign and malignant disease. Permanent recurrent laryngeal nerve palsy occurred in six (2.3%) lobectomies and transient recurrent laryngeal nerve palsy occurred in two lobectomies (< 1%). Sensitivity for detecting postoperative vocal cord immobility was 100% and specificity 85% if the end amplitude was 50% below baseline. The positive predictive value when amplitude was 50% below baseline was 18%. The negative predictive value when amplitude was 50% above or equal to baseline was 100%. Intraoperatively, the amplitude was 50% below baseline more frequently in the vocal cord immobility group (t-test, P < 0.015). No vagal nerve complications occurred. CONCLUSION: Whilst the incidence of recurrent laryngeal nerve palsy is comparable to rates in the literature, the incidence of transient palsy is lower than published averages. APS is able to reliably predict recurrent laryngeal nerve palsy based on end amplitude.